2006
DOI: 10.1590/s0004-282x2006000300012
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive improvement after treatment of depressive symptoms in the acute phase of stroke

Abstract: -The outcome of antidepressant treatment for depressive symptoms and cognitive impairm e n t at the acute phase of stroke is controversial. We investigated 93 patients, treating with citalopram 36 with s e v e re depressive symptoms (HAM-D: Hamilton Depression Rating Scale ≥18), whilst 19 patients with mild d e p ressive symptoms, and 38 non-depressed patients, remained untreated. At baseline (two weeks after s t roke), patients with severe depressive symptoms had lower scores in total Dementia Rating Scale (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…However, there was no pharmacological support, which can be considered as a positive result. In the study of Simis and Nitrini [43], where pharmacological support was used, after three months of follow up, patients who initially had mild depressive symptoms began to have higher values, where treatment was associated with improved mood, memory and attention. A prospective study with 3525 subjects, aged between 65 and 84 years, in several Italian cities, showed that older people tend to an increased risk of depression caused mainly by declining physical condition [44], thus corroborating the results of this study where inactive people tend to have an increased rate of depression.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no pharmacological support, which can be considered as a positive result. In the study of Simis and Nitrini [43], where pharmacological support was used, after three months of follow up, patients who initially had mild depressive symptoms began to have higher values, where treatment was associated with improved mood, memory and attention. A prospective study with 3525 subjects, aged between 65 and 84 years, in several Italian cities, showed that older people tend to an increased risk of depression caused mainly by declining physical condition [44], thus corroborating the results of this study where inactive people tend to have an increased rate of depression.…”
Section: Discussionmentioning
confidence: 99%
“…70 Small clinical studies have tested the utility of the antidepressant medications to improve recovery of patients with recent stroke. 50,59,60,[71][72][73][74][75][76][77][78][79][80][81] Although data are not definitive, the results generally are positive. The most important data are from the FLAME study, which was a randomized, double-blind, placebo-controlled trial of fluoxetine (20mg daily) initiated within 5 to 10 days after stroke and continued for 3 months.…”
Section: Transitioning Advances In the Understanding Of Stroke Recovementioning
confidence: 99%
“…Small clinical studies have tested the utility of the antidepressant medications to improve recovery of patients with recent stroke . Although data are not definitive, the results generally are positive.…”
Section: Transitioning Advances In the Understanding Of Stroke Recovementioning
confidence: 99%
“…However, to understand the effect of ECT on cognition, it is important to consider the neuropsychological effects of depression itself. 30,31 It seems reasonable to assume that cognitive function should similarly improve with ECT treatment in patients with depression, with or without dementia. Clinical, epidemiological and neuroimaging evidence suggest that late-life depression is associated with structural changes in the frontostriatal network that form the basis for many of the neuropsychological deficits.…”
Section: Cognitive Effectsmentioning
confidence: 99%